Conversion efficiency in re-saw wood processing mills of Akwa Ibom State, Nigeria (2011)
This study assesses the technical conversion efficiency (TCE) of thirty (30) wood re-saw mills purposively selected and grouped into six (6) locations in Akwa Ibom State. Three hundred (300) flitches obtained from fifteen (15) species of wood from Akwa Thorn State, Nigeria were examined. Variables such as wood species, flitch dimensions, saw blade thickness, sawyers' experiences and working environment factors were examined for efficiency determination. Information on operation and working environment were examined using ergonomics checklist. Data were generated using standard units of measurement, checklist and formulae. Data generated were subjected to statistical analyses using descriptive and multiple regression models. The study revealed that plank recovery ranged from 58.86% to 76.92% on individual flitch basis, percentage waste ranged from 23.08% to 28.26% and a mean plank recovery and percentages waste of 71.76% and 28.02% respectively for all sampled flitches. Variations in flitches dimension classes had significant influence on percentage wood recovery, saw dust, plank, at (P < 0.05). Significant correlation also exists between flitch dimension class and plank recovery. Noticeable variation in percentage wood recovery was observed among the various wood species. Ceiba pentandra had the highest mean plank recovery of 76.31% while Mammea africana had the least (58.31%). For reasonable reduction of wood waste generated in re-saw mills, greater use of flitches with higher thickness, routine maintenance of machines especially saw blade, experience sawyers are necessary.